(untitled) (Nexo Revista Científica, 2021)
A squall line was recorded in Dayyer port over southwest of Iran, on 19 Mar 2017. In the present paper, we have simulated the characteristic features associated with the squall line by Weather Research and Forecasting (WRF) model using five different microphysics (MP) schemes. For validating the simulated characteristics of the squall line, the latitude-height and longitude-height cross section reflectivity and precipitation value derived from observed reflectivity gathered by Doppler Weather Radar at Bushehr, synoptic weather station data at Dayyer port along with NCEP-NCAR and ERA-INTERIM reanalyzes data were used. To verify the simulated precipitation, the Fractions Skill Score (FSS) curve was calculated. Examining the simulation results for geopotential and sea level pressure show that the model simulations using different MP schemes, agree well with the verifying reanalyzes. Also, the spatial rainfall distribution of simulations and verifying observations did not show big differences. However, there are significant differences in the details of simulations such as the maximum reflectivity of the convective cells, vertical extent of the storm cells, speed and direction of the wind, rainfall values and FSS curves. Though, all of the simulations have shown convective cells over Dayyer port at the time of occurrence of the squall line, but, only the model simulation using Lin MP scheme is consistent with the corresponding radar reflectivity and vertical extent. The FSS chart showed that the skill changes with spatial scale. Results using Lin microphysics scheme crossed the FSSuniform line at lower scales when compared to other MP schemes.